THE DYNAMIC INTERPLAY OF TRADITION, IMAGE, AND SYMBOL IN SHAPING CULTURAL IDENTITY - Ubaydullayeva Sadoqat Sobirjon Qizi; Abduraimova Shabnam Zokirjon Qizi; Eshbo’riyeva Husnora Azamat Qizi (TADQIQOTLAR, 2025)
Abstract Traditions, images, and symbols are cornerstones of cultural identity, serving as conduits for preserving heritage, expressing values, and fostering community cohesion. This  study  investigates  their  interconnected  roles  through  a  qualitative  analysis  of diverse  cultural  practices,  including  rituals,  visual  arts,  and  symbolic  artifacts.  By examining case studies from Japanese, Native American, Islamic, and Indian cultures, we explore how traditions provide continuity, images convey narratives, and symbols encapsulate complex meanings.